Change and Continuity in Indonesia's Foreign Policy: Food Security Strategic Agenda from President Jokowi to Prabowo Administration - Muhammad Jullyo Bagus Firdaus (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2025)
Abstract Food security has become a part of a non-traditional international security issue. The uncertainty surrounding global crises over the past five years has increased since the COVID-19 pandemic began. Then, it was further compounded by geopolitical conflicts and supply chain disruptions. This paper analyses the dynamics of change and continuity in Indonesian foreign policy, focusing on food security under the President Joko Widodo administration and the President Prabowo Subianto administration. Additionally, this study uses a qualitative approach, drawing on document analysis and policy narratives. This study examines how Indonesia’s food security orientation has shifted during the national leadership transition, employing a change-and-continuity analysis. The research findings indicate continuity in positioning food security as a strategic national interest, while changes occur in policy orientation and framing under two different leaderships. On the one hand, in President Joko Widodo’s era, food security is constructed inwardly with the food estate program. Then, it is built outwardly through the internationalization of the issue. On the other hand, it is rearticulated inwardly as a foundation for national resilience and strategic independence, as reflected in policy articulations such as the Free Nutritious Meal Program (Makan Bergizi Gratis), which is the main strategic agenda of President Prabowo. This article argues that these dynamics reflect a pattern of change without rupture in Indonesian foreign policy, in which policy shifts occur gradually without diminishing ongoing strategic interests. Jakarta still uses an inward-looking paradigm to advance its national interests amid shifting administrations. Keywords: continuity, foreign policy change, food security, non-traditional security, Indonesia’s foreign policy. Abstrak Keamanan pangan telah menjadi bagian dari isu keamanan internasional non-tradisional. Ketidakpastian krisis global lima tahun terakhir, sejak terjadinya pandemi global COVID-19 ditambah munculnya konflik geopolitik dan gangguan rantai pasokan. Makalah ini menganalisis dinamika perubahan dan kontinuitas dalam kebijakan luar negeri Indonesia, khususnya terkait keamanan pangan dari pemerintahan Presiden Joko Widodo hingga Presiden Prabowo Subianto. Selain itu, studi ini menggunakan pendekatan kualitatif melalui analisis dokumen dan narasi kebijakan. Studi ini menunjukkan bagaimana orientasi ketahanan pangan Indonesia telah bergeser dalam konteks transisi kepemimpinan nasional, dengan menggunakan analisis perubahan dan kontinuitas. Temuan penelitian menunjukkan kontinuitas dalam memposisikan keamanan pangan sebagai kepentingan nasional strategis, sementara perubahan terjadi pada tingkat orientasi dan kerangka kebijakan dari dua kepemimpinan. Di satu sisi, pada masa pemerintahan Presiden Joko Widodo, keamanan pangan dibangun secara domestik dengan program food estate, sedangkan secara eksternal melalui internasionalisasi isu. Sementara itu, ketahanan pangan diartikulasikan kembali secara internal sebagai fondasi ketahanan nasional dan kemandirian strategis, sebagaimana tercermin dalam artikulasi kebijakan seperti Program Makan Gratis Bergizi sebagai agenda strategis utama era Presiden Prabowo. Artikel ini berpendapat bahwa dinamika ini mencerminkan pola perubahan tanpa putus dalam kebijakan luar negeri Indonesia, di mana perubahan kebijakan terjadi secara bertahap tanpa mengurangi kepentingan strategis yang berkelanjutan. Jakarta masih menggunakan paradigma yang berorientasi ke dalam negeri untuk mencapai kepentingan nasionalnya pada perubahan pemerintahan. Kata kunci: kontinuitas, perubahan kebijakan luar negeri, keamanan pangan, keamanan non-tradisional, kebijakan luar negeri Indonesia.